Akademi Sepakbola Nusantara Di Pekanbaru Dengan Pendekatan Arsitektur Tropis - Firman Swade Hutabarat; Wahyu Hidayat; Mira Dharma Susilawaty (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
As one of the countries that have high interest of football, the lack of achievement of the Indonesian national team in the international arena is a problem that must be solved if one daywant to see Indonesia in the World Cup. The main problems are in the coaching of young players which only relies on community initiatives and football competition in Indonesia is still lesscompetitive. Nusantara Football Academy is the solution of various problems related to a long time and process and substantial funds to improve football coaching system in Indonesia. With the academy is expected to produce a professional football player who can compete in the internationalarena. Pekanbaru as one of the major cities that have a lot of young talent and the high interest of football should take an active role in improving the football coaching system in Indonesia. In the design of this academy, tropical architecture approach is used to answer a variety of issues relatedto climate conditions that affect site. Some of the principles of Tropical Architecture applied in the design, such us: (1) orientation of the building; (2) Optimization of natural aeration; (3) Percentage of green spaces; (4) Responsive to environmental conditions. The concept of Total Football was chosen to solve the various problems that arise during the design process of Nusantara Football Academy. This concept is applied in all architectural design aspects of Nusantara Football Academy, such as: the order of mass, mass formation, landscaping and interior arrangement, up to building facades. Order mass efficient, simple mass formation, structuringlandscaping and attractive interior and facade that are adapted to the environmental conditions are the result of the application of the concept of Total Football in Nusantara Football Academydesign.Keywords: Football Academy, Nusantara, Tropical Architecture, Total Football.